The Eyes of Scheherazade… Looking for Meaning Between Riyadh and Teheran. Women’s Rights in Saudi Arabia and Iran - Vasileva, Evgeniya (Research Papers, 2020)
Saudi Arabia and Iran are two of the biggest countries in the world. The first is young, the second is old. The first is an aggregate of nomad and semi-nomad tribes, the second is the successor of the Persian Empire. Both are professing two different versions of Islam and rival about their regional role in the Middle East. Saudi Arabia is a kingdom Iran is a republic. Similarities between both countries are the mineral resources, the political structure, characterized with equality of the secular and of the religious leadership and the attitude towards women. The processes of modernization and urbanization in both countries lead to an over-conservative governance and to diffusion and radicalization of some of their tribal tradition in urban conditions. As a result, these are two countries where the rights and the integration of women in social significant roles and activities are strongly restricted. This article aims to present and analyze the rights and the prohibitions for the women in Iran and Saudi Arabia, their fight for reforms and its historical development.
Keywords: Economics of gender; Non-labor discrimination; Family and personal law; Human rights law